PENGARUH INSENTIF PAJAK, TARIF PAJAK, PELAYANAN FISKUS TERHADAP KEPATUHAN WAJIB PAJAK UMKM MASA PANDEMI COVID-19 - Dewi, Ni Luh Putu Maharani; Ery Setiawan, Putu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
Tax is an individual or corporate contribution to the state that is mandatory. One sector that has the potential to contribute to taxes in Indonesia is Micro, Small and Medium Enterprises (MSMEs). The current taxpayer compliance with MSMEs is still relatively low, especially at the West Denpasar KPP Pratama. The purpose of this study is to obtain empirical evidence of the effect of tax incentives, tax rates, and quality of tax service services on individual taxpayer compliance of MSMEs. The theory used in this research is the theory of planned behavior and attribution theory. A total of 100 MSME individual taxpayers were selected as respondents from 7.639 MSME individual taxpayers using the slovin formula registered at the West Denpasar KPP Pratama. The sample research method in this study was accidental sampling. The data analysis technique used is multiple linear regression analysis. The results showed that tax incentives, tax rates and tax service services had a positive effect on individual MSME taxpayer compliance during the COVID-19 pandemic. This research can provide input to the government, especially the West Denpasar Pratama Tax Service Office to improve MSME taxpayer compliance